Avaliação do tratamento com Akkermansia muciniphila BAA-835 da mucosite induzida por quimioterapia em camundongos - Ramon de Oliveira Souza (2022)
5-Fluouracil (5-FU) is a chemotherapy widely used for different types of cancer. Due to the non-selectivity of this drug, different side effects may appear in patients undergoing therapy, such as intestinal mucositis. This condition is characterized by inflammation and ulceration of the gastrointestinal mucosa, and so far there are no curative treatments, but only guidelines related to palliative interventions that seek to improve the quality of life of patients. The use of probiotics has been considered an important therapeutic strategy for the treatment of mucositis, and the bacterium Akkermansia muciniphila has stood out due to its anti-inflammatory and immunomodulatory properties. Therefore, the objective of this work was to evaluate the probiotic effect of A. muciniphila BAA 835 in a murine model of intestinal mucositis induced by 5-FU. Initially, the dose-response effect, bacterial viability and the best treatment protocol were evaluated. Subsequently, the other clinical, microbiological, immunological, histological and physiological parameters were analyzed. For this, Balb/c mice with mucositis induced with 5-FU (300 mg/Kg), in a single intraperitoneal dose, were used. Our results suggest that the best dose of probiotic was 109 CFU, in its viable form and under a preventive protocol, since in these conditions attenuation of weight loss and reduction of intestinal length was observed, in addition to the decrease in MPO and EPO levels in the tissue. Following this treatment protocol, no statistical differences were observed in the food consumption of the treated animals; however, there was a significant improvement in the clinical parameters measured using the daily disease activity index (DAI). The probiotic also improved the integrity of the epithelial barrier, decreasing intestinal permeability and bacterial translocation, in addition to contributing to the preservation of the architecture of the intestine, and attenuation of the loss of goblet cells. A. muciniphila also contributed to decreased the levels of enterobacteria in the intestine and expansion of lactic acid bacteria. In addition, a significant increase in the levels of sIgA, circulating lymphocytes, cytokine IL10, and reduction of IL6, IL1β, TNF, circulating neutrophils, hydroperoxides and the enzyme superoxide dismutase in the tissue were demonstrated. Therefore, oral administration of A. muciniphila was able to attenuate the damage caused by mucositis induced by 5-FU.